The unhealthy-tasty intuition in dining out situations: the role of health inferences and taste expectations - Garaus, Marion; Wolfsteiner, Elisabeth; Hu, Jennifer (Frontiers in Nutrition, 2023)
Increasing obesity rates around the globe have challenged policymakers to find strategies to prompt healthier eating habits. While unhealthy eating takes place in many different contexts, dining out is a context where individuals often choose an unhealthy option despite the availability of healthier alternatives. One possible explanation for this behavior is the unhealthy-tasty intuition, which refers to the belief that unhealthy food is tastier than healthy food. Nevertheless, many policymakers and restaurant managers follow the – in this context – counterintuitive approach of using health claims to nudge people towards more healthy eating choices or habits. The current research employs an online experiment and investigates how health claims and sensory claims impact on the purchase intention of healthy options for desserts. Furthermore, it explores how health inferences and taste expectations mediate the intention to purchase. Findings from the online experiment with 137 participants confirm that health claims prompt positive health inferences, while also stimulating unfavorable taste expectations, resulting in a lower intention to purchase. Surprisingly, we found no effect of a sensory claim on taste expectations. The findings of our experiment contradict the unhealthy-tasty intuition by revealing a significant positive correlation between taste expectations and health inferences. While both health inferences and taste expectations impact positively on purchasing intentions for the health-claim condition, the indirect effect of taste expectations was stronger than the indirect effect of health inferences.